Bank Dependence and Bank Financing in Corporate M&A - Huang, Sheng; Lu, Ruichang; Srinivasan, Anand (Management Science, 2022)
We examine the valuation impact of bank-financed mergers and acquisitions (M&As) and the loan contracts used to finance M&A transactions, focusing on the difference between bank-dependent acquirers and other acquirers. We find that bank-financed deals have higher acquirer’s cumulative abnormal returns relative to other cash M&A deals, but this certification effect exists only for bank-dependent acquirers. Despite bank-dependent acquirers being more susceptible to hold-up, banks do not impose higher loan pricing or more stringent nonprice terms on them. After completion of the acquisition, bank-dependent acquirers retain the M&A financing banks for a much larger share of their borrowing needs, suggesting the importance of repeat business for lack of hold-up. Our findings highlight the positive aspects of bank dependence and the importance of implicit contracting for the lack of hold-up in lending markets. This paper was accepted by David Simchi-Levi, finance.